2022
DOI: 10.3390/jrfm15030130
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Outward Foreign Direct Investment from Latin America and the Caribbean: An Integrated Entropy-Based TOPSIS Multiple Regression Analysis Framework

Abstract: Given that home country factors play a major role in the internationalization of emerging market firms, there is an ever-growing debate on how they influence the intensity of outward foreign direct investment (OFDI) from these regions. This study investigates how home country factors affect the OFDI intensity in Latin America and Caribbean (LAC) countries. We use the entropy weight method, which uses the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method and a balanced panel data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…The directionality of FID is well established in IB research (Hernández and Nieto, 2015;Konara and Shirodkar, 2018). Studies have shown that developed country firms are at an advantage when FID is towards more developed host countries, while emerging market firms know how to deal with institutional voids when operating in less developed host countries (Correa da Cunha, 2019;Correa da Cunha et al 2022b;Cuervo-Cazurra and Genc, 2011).…”
Section: Fid Moderating the Relationship Between CD And Performancementioning
confidence: 99%
See 2 more Smart Citations
“…The directionality of FID is well established in IB research (Hernández and Nieto, 2015;Konara and Shirodkar, 2018). Studies have shown that developed country firms are at an advantage when FID is towards more developed host countries, while emerging market firms know how to deal with institutional voids when operating in less developed host countries (Correa da Cunha, 2019;Correa da Cunha et al 2022b;Cuervo-Cazurra and Genc, 2011).…”
Section: Fid Moderating the Relationship Between CD And Performancementioning
confidence: 99%
“…We follow the approach proposed in previous research (Correa da Cunha, 2019; Correa da Cunha et al, 2022b;Hernández and Nieto, 2015;Konara and Shirodkar, 2018) and use a dummy variable (i.e. true or false condition) to compute distances in opposite directions separately.…”
Section: The Direction Of the Distancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparisons between countries can involve informal (Slangen and Beugelsdijk 2010) and formal institutions, including laws, regulations, and enforcement characteristics (Estrin et al 2009;Slangen and Beugelsdijk 2010). Formal institutions refer to governance mechanisms that govern and support business activity and human interaction (North 1990;Pejovich 1999;Correa da Cunha et al 2022b). However, it is wrong to compare countries based on "better" or "worse" cultural traits.…”
Section: Introductionmentioning
confidence: 99%
“…These firms operated in the 10 largest host countries in Latin America (according to GDP) over a period of 3 consecutive years ranging from 2013 to 2015. In the past few decades, Latin America has gone through profound political and economic reforms which created more favorable conditions to attract foreign firms into the region (Aguilera et al 2017;Correa da Cunha et al 2022b). These changes included the reduction in protectionist policies that were implemented during the import substitution industrialization (ISI).…”
Section: Introductionmentioning
confidence: 99%